SURGICAL TREATMENT OF MULTIPLE ISOLATED INTRAPULMONARY METASTASES - A. V. Reshetov; A. V. El’Kin; G. V. Nikolaev; O. E. Kakysheva; D. I. Kovalenko (Вестник хирургии имени И.И. Грекова, 2018)
An analysis of treatment results was made in 226 patients with multiple isolated intrapulmonary metastases of solid tumors. It appears that surgical removal of metastases was possible in patients with satisfactory functional resources and accurate evaluation in order to validate the indications for surgery. The operation shouldn’t result in considerable reduction of quality of life and didn’t prevent using other methods of treatment such as medicamental and radiation therapy. The indications to surgical intervention have to be set as individual in consideration of the number of metastases and potential of the patient to undergo the surgery.